2003
DOI: 10.1128/cdli.10.5.757-763.2003
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Presenting Cell Modulation Induces a Memory Response to p24 in Peripheral Blood Leukocytes from Human Immunodeficiency Virus-Infected Individuals

Abstract: The accurate determination of human immunodeficiency virus type 1 (HIV-1)-specific proliferative responses is critically important when evaluating immune recovery after highly active antiretroviral therapy. Using a new assay to enhance proliferative responses to recall and HIV antigen, we addressed the questions of whether viral load affects cellular immunity and whether long-term viral load suppression results in loss of antigen-specific responder cells. This assay is based on the fact that lipopolysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Therefore, it is important to understand whether HIV-infected individuals have persistent long-term memory responses to recall antigen and to measure them accurately. In an earlier study we described an assay that used LPS and monocyte adherence to augment specific proliferative responses to p24 (15). In the study described here we use this assay to evaluate proliferative responses to p24 in a HAART-suppressed cohort of infected individuals with CD4 counts greater than 300 cells/ mm 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to understand whether HIV-infected individuals have persistent long-term memory responses to recall antigen and to measure them accurately. In an earlier study we described an assay that used LPS and monocyte adherence to augment specific proliferative responses to p24 (15). In the study described here we use this assay to evaluate proliferative responses to p24 in a HAART-suppressed cohort of infected individuals with CD4 counts greater than 300 cells/ mm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies evaluating proliferative responses to human immunodeficiency virus (HIV) antigens after long periods on suppressive HAART, but the results have been equivocal (1,2,5,8,22,24,25,27). In an earlier study we demonstrated that memory cell proliferative responses to p24 antigen could be measured in a sensitive and specific manner when lipopolysaccharide (LPS) was used to drive T-cell proliferation through interactions with adherent monocytes (15). In the present study we use this assay to evaluate memory cell proliferative responses to p24 in PBL from HIV-infected individuals with suppressed viral loads (VLs) and CD4 counts greater than 300/mm 3 .…”
mentioning
confidence: 99%
“…Results from proliferation experiments have been mixed in regard to demonstrating PBL memory responses to HIV antigens from suppressed donors (2,5,9,13,47,48,50,57). The differences between these findings may be one of assay sensitivity rather than one of an inability to respond to antigen (28). A number of studies have evaluated cytotoxic T-lymphocyte (CTL) specificity in PBLs from individuals during structured interruption of suppressive HAART in HIV-1-infected individuals (4,42).…”
Section: Analysis Of Cd8mentioning
confidence: 99%